APPLICATION FRAMEWORK OF HUMAN BONE STRUCTURE OF USING MICROSOFT VISUAL BASIC 6.0 - Satrio Junianto Prayitno; Yudi Irawan Chandra, SKom, MMSI (Jurnal Sistem Informasi, 2007)
This writing describes the Application Framework of Human Bone Structures. Basically Application Framework of Human Bone Structures of this is to explain the names of the bones, the location, type, shape, relations between the bone and cause disruption to the bone. For that the author wanted to show them in computerized form using Microsoft Visual Basic 6.0. With the presents in the form of a computerized writer hopes that this application users can easily understand in studying the Framework of Human Bone Structures.